A szerző jelentősége és művével való kapcsolata hova tovább szerzői jog? - Pogácsás Anett (IUSTUM AEQUUM SALUTARE, 2014)
There are arguments that copyright law is in a danger due to its own expansion. However, not copyright law itself is expanding, but the various possibilities of creation and utilisation, resulting from the technical development. It is no longer a question whether more and more areas should be protected by copyright law. However, this is only the starting point, which can be shaded by several special circumstances. The particular relationship between authors, on the one side, and their works, on the other, undergoes significant changes from time to time, and a lot of special border-areas can be discovered, as well. It appears to be an unchallenged fact that the individual and original performance of authors needs recognition. We must admit that the potential ways of such recognition, as well as the position of authors in general, has changed a lot in recent years. There are significant differences between authors, not because of their abilities but because of a series of other important circumstances. Material benefits and personal advantages provided in relation to authors’ works may create a clear and incentive environment. These benefits and advantages shall not mean the same for every single author, while such distinction shall not lead to the demolition of copyright law, but shall serve its further development.